Existence of solutions for a critical (p1(x), …, pn(x))-Kirchhoff-type potential systems. Issue 6 (13th April 2022) - Eddine, Nabil Chems
ABSTRACT: In this paper, by using the concentration–compactness principle of Lions for variable exponent spaces and the Mountain Pass Theorem, we obtain the existence of nontrivial solutions for a class of ( p 1 ( x ), …, p n ( x ) ) -Kirchhoff-type potential systems type with critical exponent.